Probing the Natural Scene by Echolocation in Bats - Moss, Cynthia F.; Surlykke, Annemarie (Frontiers in Behavioral Neuroscience, 2010)
Bats echolocating in the natural environment face the formidable task of sorting signals from multiple auditory objects, echoes from obstacles, prey and the calls of conspecifics. Successful orientation in a complex environment depends on auditory information processing, along with adaptive vocal-motor behaviors and flight path control, which draw upon 3-D spatial perception, attention and memory. This article reviews field and laboratory studies that document adaptive sonar behaviors of echolocating bats, and point to the fundamental signal parameters they use to track and sort auditory objects in a dynamic environment. We suggest that adaptive sonar behavior provides a window to bats’ perception of complex auditory scenes.